(untitled) (Malay Literature, 2015)
Paradigms according to science and epistemology describe distinct concepts of thought patterns. For the purpose of this paper we have to understand gender paradigm. According to Gamble, a paradigm is a belief structure about the ways men and women should act and the roles they should perform. The Malaysian gender paradigm is very much controlled by religion and culture. The paradigm has shifted through time, but is the shift significant? Basically the Malay woman in Malaysia is controlled by culture and Islam. These are two prominent factors that influence her life and her interaction with fellow women, men and society. The paradigm used to be that women were weak, not as smart as men, could not lead, and were destined to be homemakers even if they were educated. An old saying goes, a woman’s place is in the kitchen, no matter how highly educated she is. This paradigm has not been challenged by women, especially by romance novel writers as will be discussed in this paper. This paper analyses two Malay novels, Tak Seindah Mimpi by Sharifah Abu Salem and Adam dan Hawa by Aisya Sofea, and looks at how the gender paradigm is portrayed vis-à-vis these two novels using the feminist theory. Keywords: new paradigm, Malay woman, romance novel, feminist theory, gender role